Inhibitory Activity and Chemical Characterization of Daucus carota subsp. maximus Essential Oils. Issue 5 (17th April 2017) - Gaglio, Raimondo; Barbera, Marcella; Aleo, Aurora; Lommatzsch, Ines; La Mantia, Tommaso; Settanni, Luca
Abstract : The essential oils (EOs) of green seeds from Daucus carota subsp. maximus growing wild in Pantelleria Island (Sicily, Italy) were characterized. EOs were extracted by steam distillation, examined for their inhibitory properties against food‐borne Gram ‐positive and Gram ‐negative bacteria and analyzed for the chemical composition by gas chromatography (GC) and mass spectrometry (MS). Undiluted EOs showed a large inhibition spectrum against Gram ‐positive strains and also vs. Acinetobacter spp. and Stenotrophomonas maltophilia . The minimum inhibition concentration ( MIC ) was in the range 1.25 – 2.50 μl/ml for the most sensitive strains. The chemical analysis indicated that D . carota subsp. maximus EOs included 34 compounds (five monoterpene hydrocarbons, six oxygenated monoterpenes, 14 sesquiterpene hydrocarbons, four oxygenated sesquiterpenes, camphorene and four other compounds), accounting for 95.48% of the total oil, and that the major chemicals were carotol, β ‐bisabolene, and isoelemicin. Abstract :